The Validity of Illegal Investments In The Digital Era On Positive Legal Arrangements In Indonesia - Taufik Noor Isya; Lamijan, Lamijan; Mohamad Tohari (UNES Law Review, 2024)
The rapid advancement of technology has transformed human behavior in numerous ways, including the widespread use of the internet, which has become an indispensable part of modern life. The internet has revolutionized various industries such as communication, trade, finance, education, and business, making it easier than ever for people to engage in online activities and even digital investments. Yet, unfortunately, many fraudulent investment opportunities have emerged, preying on unsuspecting victims and causing significant financial losses. As a result, the Indonesian government has taken measures to combat illegal investments and protect the public. Such practices are considered criminal offenses under the Criminal Code's Article 378, which criminalizes deceitful and fraudulent schemes. Additionally, fundraising without proper authorization is punishable under Article 46 of Law Number 10 of 1998 jo. Law Number 7 of 1992 concerning Banking. Sharia-based investments without a business permit from Bank Indonesia can also face legal repercussions under Article 59 of Law No. 21 of 2008 concerning Sharia Banking. These regulations aim to safeguard individuals from illegal investment activities.